Microsoft Office Communications Server 2007 R2 resource kit - Maximo, Rui (Microsoft Press, 2009)
In-depth, comprehensive, and fully revised for R2 this RESOURCE KIT delivers the information you need to deploy, manage, and troubleshoot Microsoft Office Communications Server 2007 R2. Get technical insights, scenarios, and best practices from those who know the technology best the engineers who designed and developed it along with 90+ Windows PowerShell scripts, bonus references, and other essential resources on CD. Get expert advice on how to: Plan server roles, infrastructure, topology, and security Design and manage enterprise instant messaging (IM), presence, and conferencing solutions Configure voice mail, enterprise voice, dual-forking (PBX), and VoIP Apply industry best practices for deployment Manage Unified Communications clients and devices Administer remote access, federation, and public IM Understand SIP and authentication technologies Implement a cross-team backup-and-restore plan Automate management tasks sample scripts included Monitor, diagnose, and troubleshoot problems more efficiently CD features: 90+ Windows PowerShell scripts for automating administrative tasks Office Communication Server Resource Kit tools Links to references and webcasts Understanding Microsoft Virtualization Solutions eBook Four appendixes, including Windows PowerShell functions, Direct SIP with IP-PBX, and A/V troubleshooting Bonus content Chapters from 15 related Microsoft Press books Fully searchable eBook of this guide.